Ultra-low-fat Muscovy duck (Cairina moschata) ham with grapefruit (Citrus × paradisi L.) albedo flour - Velásquez-Rivera, Jorge Ruperto (2025)
Introduction. Sausages are products consumed worldwide that allow for the use of different types of meat and underutilized raw materials, such as grapefruit (Citrus × paradisi L.) albedo, a by-product of the citrus industry that contains fiber and important antioxidant substances for human health. Objective. To evaluate the effect of adding debittered grapefruit albedo flour on the physicochemical, sensory, and microbiological characteristics of ultra-low-fat Muscovy duck (Cairina moschata) ham. Materials and methods. The study was conducted at the Faculty of Technical Education for Development at the Universidad Católica de Santiago de Guayaquil, Ecuador, between September 2022 and August 2023. Four treatments were formulated with the addition of 0 %, 2 %, 4 %, and 6 % grapefruit albedo flour. The hams were evaluated for physicochemical parameters (pH, titratable acidity, moisture content, ash, protein, fiber, fat, total phenols, and antioxidant capacity), technological properties (emulsion stability, yield, and water-holding capacity), and sanitary parameters (aerobic mesophilic microorganism count, Escherichia coli, Staphylococcus aureus, and Salmonella). In addition, texture profile and sensory analyses (acceptance test, purchase intention, and check-all-that-apply) were performed with 41 consumers. Results. The products complied with sanitary and compositional standards. The addition of grapefruit albedo flour increased antioxidant capacity, fiber content, and water-holding capacity. All products received a rating equivalent to “I moderately like it,” and hardness and elasticity decreased as flour content increased, without affecting texture acceptance. Conclusions. It is possible to produce Muscovy duck hams incorporating up to 6 % debittered grapefruit albedo flour, achieving good acceptance, higher fiber content, and antioxidant capacity.